2004
DOI: 10.4049/jimmunol.172.12.7393
|View full text |Cite
|
Sign up to set email alerts
|

Host Dendritic Cells Alone Are Sufficient to Initiate Acute Graft-versus-Host Disease

Abstract: Alloantigen expression on host APCs is essential to initiate graft-vs-host disease (GVHD); however, critical APC subset remains to be elucidated. We compared the ability of dendritic cells (DCs) and B cells to initiate acute GVHD by an add-back study of MHC class II-expressing APCs (II+/+) into MHC class II-deficient (II−/−) mice that were resistant to CD4-dependent GVHD. Injection of host-derived, but not donor-derived, II+/+ DCs or host-derived II+/+ B cells, was sufficient to break GVHD resistance of II−/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
170
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(176 citation statements)
references
References 34 publications
4
170
2
Order By: Relevance
“…Several mouse model experiments have revealed that transfer of IL-17-producing cells induced acute GVHD, [33][34][35] whereas in contrast there is a report 31 showing that donor IL-17-producing cells ameliorated acute GVHD. Host DCs are critical in the initiation of acute GVHD, [52][53][54] leading to a hypothesis that IL-17-producing cells could modify the function of host DCs through unknown mechanisms. Direct interaction between IL-17 and host DCs may be supported by the fact that DCs expressed IL-17 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several mouse model experiments have revealed that transfer of IL-17-producing cells induced acute GVHD, [33][34][35] whereas in contrast there is a report 31 showing that donor IL-17-producing cells ameliorated acute GVHD. Host DCs are critical in the initiation of acute GVHD, [52][53][54] leading to a hypothesis that IL-17-producing cells could modify the function of host DCs through unknown mechanisms. Direct interaction between IL-17 and host DCs may be supported by the fact that DCs expressed IL-17 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason reduced intensity conditioning causes less aGVHD as there is decreased damage from the conditioning regimen to the host tissue leading to less activation of the immune cascade [24,25]. In nonclinical models GVHD can be reduced via manipulation of APCs as well [26,27]. Also non-hematopoietic cells such as mesenchymal stromal cells have been shown to decrease the activity of alloreactive T cells leading to reduced GVHD although the mechanism of such interaction is poorly understood at this time [28].…”
Section: Pathophysiologymentioning
confidence: 99%
“…5 To mount an efficient alloresponse, antigens need to be presented by professional antigen presenting cells (APCs) with host APCs being crucial for the initiation of GVHD. [6][7][8][9][10] Depletion of APCs in the liver and the spleen significantly inhibits the recruitment and proliferation of donor T cells, 11 and the elimination of Langerhans cells seems to be efficient in preventing skin GVHD. 12 However, there is also increasing evidence implicating crosspresenting donor APCs in acute 13 and chronic 14 GVHD.…”
Section: Introductionmentioning
confidence: 99%